Dispersion of fullerene-like WS2 nanoparticles within epoxy and the resulting fracture mechanics. (23rd November 2015) - Haba, Dietmar; Brunner, Andreas J.; Pinter, Gerald
Abstract: Fullerene-like WS2 (IF-WS2 ) nanoparticles (NPs), some with silane-based surface functionalization, were dispersed within epoxy as toughening agents. Dispersion by sonication resulted in a broad and likely bimodal agglomerate size distribution and in thermo-oxidative degradation. In contrast, three-roll milling gave good and well reproducible dispersion quality as measured by dynamic light scattering (DLS). The fracture toughness increased considerably, independently of the functionalization. Atomic-force microscopy indicated that the epoxy's modulus close to the NPs did not differ from the bulk modulus, thus modulus inhomogeneities cannot explain the toughness increase. Fracture surfaces show curved crack lines several hundred nanometers distant from the NPs, which are likely due to secondary cracks induced at the nanoparticle surfaces. The resulting increase in the fracture surface area and possible shear fracture are likely toughening mechanisms.